Analysis of the language of Pedagogy. Characterization and typology - Soler Costa, Rebeca (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
Knowing the language of a scientific discipline allows a better understanding of its epistemology. The pedagogical language needs analysis, since it has not been studied. Therefore, the aim of this article is to show the linguistic characterization of the language of Pedagogy. A literature review of the concept of «special languages» is developed and an analysis of the lexis and the extra linguistic factors is carried out. It is used a qualitative research methodology, in a descriptive dimension. The results show that it is a «sector language». The characterization of the lexis and pragmatic factors shows that this language belongs to a «threshold level». This characterization allows to know how Pedagogy builds its language, how its speakers convey the meanings.